Exploring the influence of cultural participation on the subjective well-being of victims in Mexico - Reyes-Martínez, Javier; Martínez-Martínez, Oscar A.; Lombe, Margaret; Piñeros-Leaño, María (Frontiers in Psychology, 2023)
Introduction Considering the increasing incidence of crime in Mexico, it is necessary to understand the strategies that individuals utilize in response to victimization and the effects of this on their subjective well-being. Methods A generalized structural equation modeling (GSEM) analysis with data from the 2012 Self-reported Well-Being Survey (BIARE, n = 10,654); dependent variables: subjective well-being (i.e., cognitive well-being and affective balance); independent variables: self-reported victimization (i.e., by domestic violence, community violence, and structural violence) and cultural participation (i.e., cultural attendance, engagement, and consumption). Results Results show an overall positive and statistical influence of the cultural participation activities on the subjective well-being of victims of community and structural violence (but not of domestic violence), because, for those who reported higher levels of cultural participation, the probability of better subjective well-being were higher. Conclusions Victims potentially coped and adapted to stressful and traumatic situations (i.e., experiences of victimization) via cultural participation activities. However, there are distinctive effects according to different forms of violence, which may be accounted for in formulating public policies related to victims. This has implications for scholars, policymakers, and practitioners in improving the general quality of life of victims and the general population.